Chromatin remodeling enzymes: who's on first? - Fry, C.J.; Peterson, C.L. (Current Biology, 2001)
A central problem in the regulation of eukaryotic gene expression is understanding how gene-specific transcriptional activators orchestrate the recruitment of the myriad proteins that are required for transcription initiation. An emerging view indicates that activators must first target two types of chromatin remodeling enzyme to the promoter region: an ATP-dependent SWI/SNF-like complex and a histone acetyltransferase. These two enzymes appear to act synergistically to establish a local chromatin structure that is permissive for subsequent events. Furthermore, several recent studies indicate that the recruitment of chromatin remodeling enzymes must follow an obligatory, sequential order of events that is determined by either promoter context or cell-cycle position. Here we review recent developments concerning the role of chromatin remodeling enzymes in gene regulation, and propose several models to explain how different chromatin remodeling activities can be functionally coupled.